2021
DOI: 10.2147/copd.s290805
|View full text |Cite
|
Sign up to set email alerts
|

Are COPD Prescription Patterns Aligned with Guidelines? Evidence from a Canadian Population-Based Study

Abstract: Background In contemporary guidelines for the management of Chronic Obstructive Pulmonary Disease (COPD), the history of acute exacerbations plays an important role in the choice of long-term inhaled therapies. This study aimed at evaluating population-level trends of filled inhaled prescriptions over the time course of COPD and their relation to the history of exacerbations. Methods We used administrative health databases in British Columbia, Canada (1997–2015), to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Conversely, the treatment patterns observed may be consistent with NICE guidelines, which recommend initiatingtreatment with ICS/LABA dual therapy in patients withasthmatic features 5. This is in line with several studies that have shown disparities between international treatment recommendations and national prescribing practices in the UK and in other countries 20–24…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, the treatment patterns observed may be consistent with NICE guidelines, which recommend initiatingtreatment with ICS/LABA dual therapy in patients withasthmatic features 5. This is in line with several studies that have shown disparities between international treatment recommendations and national prescribing practices in the UK and in other countries 20–24…”
Section: Discussionsupporting
confidence: 91%
“…5 This is in line with several studies that have shown disparities between international treatment recommendations and national prescribing practices in the UK and in other countries. [20][21][22][23][24] Disparities between a particular set of recommendations and prescribing practices in primary care may be related to variation in familiarity and implementation across different international, national and local guidelines. 23 25 In support of this, we observed geographical variation in prescribing patterns, with most prevalent and incident users located in western regions, likely due to differing practices across local clinical commissioning groups and the greater representation of patients in these regions in the CPRD-Aurum database.…”
Section: Open Accessmentioning
confidence: 99%
“…Our results concur with other recent studies that confirmed the association between symptoms and ICS prescription. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Our results concur with other recent studies that confirmed the association between symptoms and ICS prescription. 29,30 Understanding the role of eosinophils in COPD has increased over the last years. 31 Within our sample, blood eosinophils were not associated with ICS use, which in addition to the significant proportion of patient with missing eosinophil counts, could be suggesting a lack of awareness of the usefulness of eosinophil counts for the management of COPD within primary care.…”
mentioning
confidence: 99%
“…Among patients with advanced COPD, those figures dropped to 59% and 69%, respectively [ 9 ]. A recent Canadian study of prescription patterns for COPD found overprescribing of inhaled corticosteroids and underprescribing of LABD [ 14 ]. In contrast, our analyses showed a very high proportion of COPD patients having ever received a prescription for LABD during the study period for both spirometry-based and hospitalization-based definitions of COPD.…”
Section: Discussionmentioning
confidence: 99%